2000
DOI: 10.1890/1051-0761(2000)010[1090:msaoac]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Stock Analysis of Atlantic Cod Near the Gulf of St. Lawrence Based on Microsatellite Dna

Abstract: The collapse of various stock complexes of cod (Gadus morhua) in the northwest Atlantic has prompted a clarification of relationships among stock components. Here we examine the genetic composition of >2300 cod collected during 1994–1997 in the Gulf of St. Lawrence and its approaches to determine whether: (1) stock components can be genetically identified; (2) population structure is temporally stable; (3) components are always separated and, if not, where and when are they mixed; and (4) component contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 70 publications
3
45
1
1
Order By: Relevance
“…Such effects are, however, expected to contribute little to allele frequency variation in marine organisms with extensive overlap between generations and the presumed very large effective population sizes. Our analysis comprised populations exhibiting lower differentiation than MSA studies in most other marine species (Wirgin et al 1997, Ruzzante et al 2000, Beacham et al 2008, Wennevik et al 2008) and approximately an order of magnitude lower than MSA studies in salmonids (Ruzzante et al 2004, Beacham et al 2005, Koljonen et al 2005, Smith et al 2005, Gauthier-Ouellet et al 2009). Using BAYES with data for 8 microsatellite loci typed in 26 Atlantic salmon populations, Koljonen et al (2005) reported that deviation between true and estimated single population contributions averaged 3% in a composite self-assignment test (i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such effects are, however, expected to contribute little to allele frequency variation in marine organisms with extensive overlap between generations and the presumed very large effective population sizes. Our analysis comprised populations exhibiting lower differentiation than MSA studies in most other marine species (Wirgin et al 1997, Ruzzante et al 2000, Beacham et al 2008, Wennevik et al 2008) and approximately an order of magnitude lower than MSA studies in salmonids (Ruzzante et al 2004, Beacham et al 2005, Koljonen et al 2005, Smith et al 2005, Gauthier-Ouellet et al 2009). Using BAYES with data for 8 microsatellite loci typed in 26 Atlantic salmon populations, Koljonen et al (2005) reported that deviation between true and estimated single population contributions averaged 3% in a composite self-assignment test (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…However, when detailed sampling of the main populations contributing to mixed aggregations is attainable, approaches can be designed to overcome problems with low genetic resolution among populations (see e.g. Ruzzante et al 2000Ruzzante et al , 2006.Atlantic herring Clupea harengus L. is an abundant and widely distributed marine pelagic fish that spawns on substrate in coastal areas throughout most of the north Atlantic (Iles & Sinclair 1982). Most herring populations are migratory and often congregate on common feeding and wintering grounds where aggregations may consist of mixtures of individuals from several populations.…”
mentioning
confidence: 99%
“…There is growing recognition that many marine fish stocks consist of amalgamations of several geographic components (35,36). It would seem prudent to try to prevent loss of such stock components, including those that appear, at present, to be unproductive.…”
Section: Discussionmentioning
confidence: 99%
“…There would therefore be a need to identify the relative contributions from putative stocks, such that they can be monitored independently. Indeed, Ruzzante et al (2000b), working on stock complexes of cod in the north-western Atlantic have demonstrated the efficacy of a mixed-stock-analysis approach based on 6 polymorphic microsatellite loci. It was possible not only to estimate the proportion of cod contributions from various stock components, but also to demonstrate temporal stability of structuring over a 2 yr period.…”
Section: Implications For Fishery Monitoring and Future Managementmentioning
confidence: 99%